Implementasi Metode Pembelajaran Mind Mapping Untuk Meningkatkan Aktivitas dan Hasil Belajar Peserta Didik pada Pembelajaran Biologi Kelas XI IPA 3 SMAN 1 Pinrang - Yamin, Muhammad Richsan (Biology Teaching and Learning, 2019)
Abstract. Improving the quality of education through the research of classroom action research which aim to improved learning activities and learning outcomes of learner through applied the learning method of mind mapping in structure and function of animal tissue. The subject of this researched was learners of XI IPA 3 SMAN 1 Pinrang which total 48 learners of school year 2017/2018. Qualitative data which investigated was learning activities observed by observer since learning process, while the quantitative data obtained from the score of making mind mapping, essay test and learning evaluation test. The result of this researched showed that there is enhancement of learning activities on the 1st cycle showed the percentage of learners was 72% for at all indicators which was observed, while on the 2nd cycle enhancement learning activities percentage of learners was 100%. For at all indicators which was observed. The outcomes of learner’s data obtained in the 1st cycle with total the learners not complete was 18 people with percentage 38%, while the outcomes of learners complete was 30 people with percentage 63%. While the outcomes of learners in the 2nd cycle increased with the learners not complete was 6 people with 13%, while the outcomes of learners complete was 42 people with percentage 88%. Keywords: Classroom action research, Mind mapping learning activities, learning outcomes.